Evolution of the Antibiotic Resistance Levels, Multi-Resistance Patterns, and Presence of Antibiotic Resistance Genes in E. coli Isolates from the Feces of Breeding Hens during the Rearing Period - Alejandro Fenollar-Penadés; Pablo Catalá-Gregori; Vicente Tallá-Ferrer; María Ángeles Castillo; Miguel García-Ferrús; Ana Jiménez-Belenguer (MDPI AG, 2024)
The food chain acts as an entry point for antibiotic resistance to reach humans and environment. Because of the importance of the poultry sector, we investigated the prevalence and evolution of antibiotic resistance in Escherichia coli isolates from a series of 14,500 breeding hens and their farm environment during the rearing period. Samples included meconium from one-day-old breeders and fecal samples and boot swabs from the breeding sheds of pullets and adult hens. All E. coli isolates from one-day-old chicks, 77% from feces and 61% from boot swabs, were resistant to at least one antibiotic. Cefotaxime and multi-drug resistance in fecal isolates decreased during the rearing period from 41.2% and 80.8% in one-day-old chicks to 3.8% and 33.8% in adults. All genes studied were detected in E. coli from feces and boot swabs, the most common being blaTEM (75%), blaSHV (72%), and qnrB (67%). blaCMY-2 was detected in 100% of one-day-old breeders. The combination of at least one cephalosporin and one quinolone resistance gene was detected in 68.7% of fecal and boot swab isolates. Our results highlight the need to monitor the prevalence of antibiotic resistance on farms and to take appropriate measures to reduce the risk to public and environmental health.